Correlation between parasitemia and spleen size in patients with P. falciparum infection - Dini Lailani; Munar Lubis; Bidasari Lubis; Syahril Pasaribu (Paediatrica Indonesiana, 2004)
Background Spleen is an important organ in immunity to malariainfection which is always affected in malaria patients. Enlargementof the spleen is one of the main clinical symptoms of malaria. Levelof parasitemia is related to the risk of complications.Objective To describe the correlation between parasitemia andspleen size in patients with P.falciparum infection.Methods One hundred and four patients including children andadults with fever, pale, jaundice, diarrhea, and headache who vis-ited public health centers in 5 villages in Mandailing Natal, NorthSumatera were enrolled in this study. The diagnosis of malariawas based on blood smears stained by Giemsa method, while thespleen size was measured using Hackett method. Correlation be-tween parasitemia and spleen size was tested by Spearman rankcorrelation.Results Splenomegaly was found in 37 of 104 patients (35.6 %)with the size of H1 in 10.6 %, H2 in 15.4 %, H3 in 9.6 %. The meanparasite count between patients with and without splenomegalywas different, and the difference was significant between patientswith spleen size of H0 and H3. The higher the parasitemia, thebigger the spleen size was (r=0.291; p=0.03).Conclusion There was a correlation between parasitemia andspleen size in falciparum malarial infection